The Notion of Love as the Keystone of All Humanities: An Argument in Defense of an Academic Discipline from Selected Medieval and Eighteenth-Century Poetry - Classen, Albrecht (Unisia, 2024)
For many people it seems to be a simple and resolute strategy to reject the justification of the Humanities as part of a university curriculum so that money, time, and energy could be saved for more important matters leading directly to a career beyond college. Emotions such as erotic love are, so they say or imply, irrelevant for our postmodern society and don’t need to be studied in whatever discipline. Instead, we must work toward figuring out how to engage with economic issues, how to develop new technologies, how to ensure high employment rates, and how to make the money flow in a stable process. All this, however, ignores what really matters in our existence here on earth, primarily love, a force that tantalizes, confuses, paralyzes, and stuns us whenever it occurs, and it elates and inspires us, giving us happiness and sorrow, pain and excitement, all depending on the circumstances. As this paper will argue, perhaps carrying the proverbial owls to Athens, without love, there is no real life. The entire discourse of love since late antiquity, throughout the Middle Ages, the Renaissance, and subsequently until today, has always forced us to acknowledge the essence of human existence, fundamentally predicated on the notion of love, unrequited or fulfilled, in marriage or in an extramarital relationship. The literary discourse demonstrates that throughout time, the interest in the topic of love has been a universal concern, and keeping that in mind, we suddenly hold the most powerful tool in our hand to defend the Humanities within the academic framework. The key consists of the realization that there is hardly anything more important to study at any level of people’s lives than love because it provides meaning, happiness, relevance, and community. Of course, it is important also to keep in mind a number of other values and ideals, such as justice, humility, fairness, tolerance, and then also, at least for some people, love of God, and fear of death. There are many media to reflect on love, but poetry has commonly been the most crucial narrative platform to explore this highly complex and challenging phenomenon and to provide expression and imagery for the ineffable experience that is certainly with us, whether people acknowledge it or not. After some reflections on what constitutes the core responsibility of research and teaching in the Humanities, this paper examines a small selection of diverse love poems from two time periods to illustrate their deep and universal impact on human existence and, hence, their relevance for all of us.